2017
DOI: 10.17503/agrivita.v39i3.1171
|View full text |Cite
|
Sign up to set email alerts
|

Development of Simple-Sequence Repeats Markers from Durian (Durio zibethinus Murr. cultv. Matahari) Genomic Library

Abstract: Simple sequence repeats have been proved as powerful markers and widely used in molecular breeding to reduce cycles and cost efective. The availability of the marker is, however, very limited in durian. This research aimed to develop SSR markers from durian genomic library. Genomic DNA was isolated from durian shoot leaf, whilst SSR motifs were isolated using membrane-based oligonucleotide enrichment hybridization protocol. Annotation made on the library found 527 unique motifs from 354 durian libraries which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…As far as we are aware, this is one of few studies that have used SSR markers to evaluate genetic variation in durian. A study by Santoso et al (2017) reported the development of SSR markers for the study of genetic variation in durian. However, none of the 11 markers reported contained perfect repeat motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, this is one of few studies that have used SSR markers to evaluate genetic variation in durian. A study by Santoso et al (2017) reported the development of SSR markers for the study of genetic variation in durian. However, none of the 11 markers reported contained perfect repeat motifs.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have used SSR markers to study the genetic variation in durian (e.g., Sales, 2015 ; Santoso et al, 2017 ). In this study, SSR markers were designed from publicly available DNA sequences containing SSR regions, and used to study the genetic variation among major durian types found in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Identifikasi tentang kebenaran suatu genotipe tanaman menggunakan marka yang tidak terpaut adalah salah satu metode yang bisa digunakan dalam menilai kemurnian benih hibrida serta satu penanda yang polimorfik sudah dapat dikatakan cukup untuk menguji kemurnian benih (Yashitola et al 2002). Penggunaan marka SSR telah dilakukan untuk identifikasi variasi genetik tanaman durian (Sales, 2015), Santoso et al, 2017) dan Siew et al (2018).…”
Section: Introductionunclassified